2024
DOI: 10.1002/eco.2650
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of sap flux density of oak in a humid region in China

Yujie Liu,
Zhengbing Chen,
Lei Cheng
et al.

Abstract: Transpiration plays a vital role in determining the watershed water cycle. However, we still have little knowledge of the characteristics of tree transpiration in the Hanjiang River Basin, which is the water source for the middle route of South‐to‐North water diversion project. Here, we measured sap flux density of oak trees (Quercus, the dominant species here) at the 10‐min resolution for 2 years and explored its response to the environmental conditions. The incoming short‐wave radiation and vapour pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 100 publications
0
0
0
Order By: Relevance
“…Equations 1 and 2 set the basis for the general mathematical expression of hysteresis indicated by a time lag (Zhang et al, 2014). Figure 1b shows that the response of SF to Rsi can be characterized by a closed counterclockwise hysteresis loop, which is reported in previous studies in the literature (e.g., Liu et al, 2024;Wan et al, 2023;Wang et al, 2019). However, some studies have reported SF might advance Rsi as aforementioned (e.g., Wan et al, 2023;Zha et al, 2017).…”
Section: Modified Mathematical Representations Of the Hysteresis Phen...mentioning
confidence: 64%
See 1 more Smart Citation
“…Equations 1 and 2 set the basis for the general mathematical expression of hysteresis indicated by a time lag (Zhang et al, 2014). Figure 1b shows that the response of SF to Rsi can be characterized by a closed counterclockwise hysteresis loop, which is reported in previous studies in the literature (e.g., Liu et al, 2024;Wan et al, 2023;Wang et al, 2019). However, some studies have reported SF might advance Rsi as aforementioned (e.g., Wan et al, 2023;Zha et al, 2017).…”
Section: Modified Mathematical Representations Of the Hysteresis Phen...mentioning
confidence: 64%
“…The hysteresis response of SF (or other evapotranspiration components) to the key meteorological drivers (i.e., Rsi and VPD) has been widely reported in the literature over the last few decades, attracting extensive attentions to exploring the onset, underlying mechanisms and implications of these hysteresis phenomena (Dhungel et al, 2021;Xu et al, 2022;Zhang et al, 2014Zhang et al, , 2019b. When exploring the response of SF to Rsi and VPD, a clear hysteresis loop emerges when SF is plotted against Rsi and VPD on a diurnal basis (Liu et al, 2024;Wan et al, 2023). Such diurnal hysteresis patterns of SF or evapotranspiration are usually complicated, and it is difficult to describe these relationships with simple mathematical functions, limiting our abilities to accurately quantify forest water use (Bai et al, 2017;Tu et al, 2019;Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%